Sources and preferences for nutrition information among older adults: A scoping review - Jane McClinchy; Angela Dickinson; Emily Barnes; Tai Ibitoye; John Jackson; Amander Wellings (PLoS ONE, 2026)
A nutritionally adequate diet is essential for older adults to support healthy ageing and reduce the risk of malnutrition. With over a million older adults in the UK affected or at risk, understanding where they source nutrition information is critical for designing effective public health interventions. This scoping review mapped existing studies on the sources and preferences for nutrition information among older adults. A comprehensive search of PUBMED, Scopus, and CINAHL (March 2023; updated February 2025) yielded 8936 records, of which 15 studies reporting on 14 research projects met inclusion criteria. The majority of studies reported on multiple sources including magazines, family and friends, television, dietitians, general practitioners, internet and embodied knowledge (hidden and unconscious gained from personal experience). Educational level, gender, and trust were found to influence uptake and use. Further research is needed to assess the impact of these information sources and identify strategies to support older adults in making informed food choices that promote healthy ageing.